2009
DOI: 10.5194/acp-9-9491-2009
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and crystalline aerosol particles interacting with water vapor: conceptual framework and experimental evidence for restructuring, phase transitions and kinetic limitations

Abstract: Abstract. Interactions with water are crucial for the properties, transformation and climate effects of atmospheric aerosols. Here we present a conceptual framework for the interaction of amorphous aerosol particles with water vapor, outlining characteristic features and differences in comparison to crystalline particles. We used a hygroscopicity tandem differential mobility analyzer (H-TDMA) to characterize the hydration and dehydration of crystalline ammonium sulfate, amorphous oxalic acid and amorphous levo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
709
4
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(809 citation statements)
references
References 201 publications
73
709
4
1
Order By: Relevance
“…However, a value of t hg of this order can impact results inferred from aerosol instruments with residence times of seconds, such as the hygroscopicity tandem differential mobility analyzer (HTDMA) 15,32 and cloud condensation nuclei counter (CCNC). 42 D H 2 O is estimated to decrease to values as low as 10 À20 cm 2 s À1 at temperatures characteristic of the middle to upper troposphere, resulting in kinetic limitations of water mass transport with t hg E hours to days.…”
Section: Hygroscopic Growth Timescale Of Soamentioning
confidence: 99%
See 2 more Smart Citations
“…However, a value of t hg of this order can impact results inferred from aerosol instruments with residence times of seconds, such as the hygroscopicity tandem differential mobility analyzer (HTDMA) 15,32 and cloud condensation nuclei counter (CCNC). 42 D H 2 O is estimated to decrease to values as low as 10 À20 cm 2 s À1 at temperatures characteristic of the middle to upper troposphere, resulting in kinetic limitations of water mass transport with t hg E hours to days.…”
Section: Hygroscopic Growth Timescale Of Soamentioning
confidence: 99%
“…[14][15][16][17] Aqueous solutions of a number of organic substances tend to form semi-solid or amorphous solid (glassy), rather than crystalline, phases as humidity decreases. 15 Ambient particles in boreal forests as well as laboratory-generated particles, consisting predominantly of SOA, have been observed to bounce off the smooth hard surface of an inertial impactor, implying a non-liquid state. 18,19 Upon dilution or heating, SOA particles can evaporate unexpectedly slowly, as a result of retarded mass transfer from the particle bulk to the surface, characteristic of semi-solid behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mikhailov et al suggested that this scenario could lead to higher observed g m values at 300 high RH since the observed initial particle mass will be lower than the theoretical one due to 301 water adsorption being surface limited. 42 Tables S5-S7. 319 The size-based growth factors of the atmospheric particles ( Figure S2 and Table S9, 320 Supporting Information) yield very different growth curves.…”
Section: Aiomfac 294mentioning
confidence: 99%
“…42 Higher 349 values of κ correspond to higher hygroscopicity and for atmospherically relevant particles κ 350 typically ranges from 0 to values exceeding 1. However, instead of a ratio of volumes mass-351 based growth factors can also be used to calculate κ by assuming particle density.…”
Section: Hygroscopicities 345mentioning
confidence: 99%